2005
DOI: 10.1158/0008-5472.can-05-2528
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the MutL Homologue hMLH3 in Human Cells and its Role in DNA Mismatch Repair

Abstract: The human mismatch repair (MMR) proteins hMLH1 and hPMS2 function in MMR as a heterodimer. Cells lacking either protein have a strong mutator phenotype and display microsatellite instability, yet mutations in the hMLH1 gene account for f50% of hereditary nonpolyposis colon cancer families, whereas hPMS2 mutations are substantially less frequent and less penetrant. Similarly, in the mouse model, Mlh1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(154 citation statements)
references
References 34 publications
7
141
0
3
Order By: Relevance
“…This assumption originally suggested by results from the yeast studies (13) was recently supported by the study, in which a heterodimer of Mlh1 and Mlh3 was shown to contribute to mechanisms of tumour suppression in the mouse (14). Furthermore, a human homologue, hMutLÁ (hMLH1/ hMLH3) was shown with low efficiency to be able to repair mismatches in vitro (15). Since MMR occurs in the nucleus, to be functional in vivo, hMLH3 ought to localize in the nucleus.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This assumption originally suggested by results from the yeast studies (13) was recently supported by the study, in which a heterodimer of Mlh1 and Mlh3 was shown to contribute to mechanisms of tumour suppression in the mouse (14). Furthermore, a human homologue, hMutLÁ (hMLH1/ hMLH3) was shown with low efficiency to be able to repair mismatches in vitro (15). Since MMR occurs in the nucleus, to be functional in vivo, hMLH3 ought to localize in the nucleus.…”
Section: Introductionmentioning
confidence: 83%
“…HeLa cells express hMLH3, hPMS2 and hMLH1, while HCT116 lacks hMLH1 and hPMS2 (15). HeLa cells were cultured in MEM + Earle's medium (Invitrogen/Gibco) and HCT116 cells in McCoy's 5a media (Invitrogen/Gibco) with 10% fetal bovine serum (Invitrogen/Gibco) at 37˚C in a 5% CO 2 -humidified atmosphere.…”
Section: Human Cell Linesmentioning
confidence: 99%
“…The human MLH3 gene was first identified approximately in the year 2000, and it is located on 14q24.3 chromosome with a coding length of 4.3 kb, composed of 12 exons, of which exon 1 is 3.3 kb, accounting for 75 % of the coding region [3]. It is a member of a conserved protein family, which is involved in the DNA mismatch repair and meiotic recombination mechanism [4,5]. Furthermore, MLH3 was found to interact with MLH1 [12].…”
Section: Discussionmentioning
confidence: 99%
“…It was found on 14q24.3 chromosome with a coding length of 4.3 kb [3]. Its basic role is in the DNA mismatch repair mechanism, while it has been proposed to play a distinct role in the meiotic recombination mechanism [4,5]. Inactivation of the MLH3 gene has been suggested to play a role in both male and female infertility [3] since the presence of the MLH3 C2531T polymorphism leads to an increased risk for developing infertility [6].…”
Section: Introductionmentioning
confidence: 99%
“…Other MutL homologues, MutLβ (MLH1/PMS1) and MutLγ (MLH1/MLH3), are surmised to participate in the repair of some base-base mispairs and IDLs and may be partially redundant with MutLα (see (Cannavo et al, 2005).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%